Memadupadankan antara Kompetensi Konselor aspek Asesmen BK dengan Pengembangan Literasi Siswa di Sekolah - Catharina Tri Anni; Ninik Setyowani; Kusnarto Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2018)
The global development of the 21st century demanding students ability to be more critical, analytical and creative, so the school have a role as an instrument to shape that personality. School literacy movement is one effort to answer the demands. Through literacy students are conditioned to intelligently analyze, construct mindsets, which ultimately generate critical and dignified behaviors in the deal with the times changing. Student behavior is formed through the conditioning of school environments involving multiple parties, including guidance and counseling teachers. The guidance and counseling teacher should be able to translate the needs of the students to develop literacy skills through programs designed for students. Guidance and counseling teachers are able to integrated student literacy development procedures in classroom learning with services provided to students, so that the development of this literacy is integrated with guidance and counseling services.